Development of CaO/PVA Catalyst from Fish Bone for Biodiesel Production - Sarina Sulaiman; Nor Fatin Abdul Jamaludin; Nassereldeen Ahmed Kabbashi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
In this study, calcium oxide were synthesized from fish bone waste and the optimum condition : catalyst amount, temperature and methanol to oil ratio (molar) for biodiesel production were studied. The calcium oxide (CaO) derived from fish bone wastes was then supported on polyvinyl alcohol (PVA) to easily separate the catalyst and biodiesel. Fish bone were dried in oven at 70 oC for 24 hr before calcination process at 900 oC for 4 hours. The biodiesel yield was studied by varying three parameters, namely methanol to oil ratio (molar) (6:1 - 20:1), amount of catalyst (1-10 wt%) and temperature (55-65 oC). The highest yield obtained from this study was at 80.40 % with catalyst amount of 10 wt%, methanol to oil ratio (molar) of 20:1 and temperature of 65 oC.